Wage Determination and Returns to Education in Urban China, 1995 - Wan, Fan (Université d'Ottawa | University of Ottawa, 2004)
This paper examines wage determination and returns to education in urban China, using the most recent available micro-level data from the Chinese Household Income Project 1995 released by " The Inter-universities Consortium for Political and Social Resear